2005
DOI: 10.1038/modpathol.3800427
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and activated epidermal growth factor receptor expression in gastrointestinal carcinoids and pancreatic endocrine carcinomas

Abstract: The epidermal growth factor receptor (EGFR) plays an important role in the pathogenesis of many tumors. To analyze the expression of EGFR and activated EGFR in well-differentiated neuroendocrine carcinomas including primary and metastatic gastrointestinal carcinoid tumors and pancreatic endocrine tumors (PET), we examined 58 gastrointestinal carcinoid tumors and 48 PET using immunohistochemistry, Western blotting, and RT-PCR. EGFR and activated EGFR (P-EGFR) were expressed by both gastrointestinal carcinoids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 18 publications
0
60
3
Order By: Relevance
“…Studies examining EGFR expression have noted significantly worse prognosis in NETs expressing EGFR rather than those that do not (20). This does not appear to be the case in our study, with over >80% of cases expressing EGFR and these tumours did not show a worse prognosis.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Studies examining EGFR expression have noted significantly worse prognosis in NETs expressing EGFR rather than those that do not (20). This does not appear to be the case in our study, with over >80% of cases expressing EGFR and these tumours did not show a worse prognosis.…”
Section: Discussioncontrasting
confidence: 43%
“…Recent studies have shown that HER family of receptors play a critical role in progression of various cancers (17)(18)(19). Previous studies have demonstrated the expression of EGFR in NETs (13,20). We have previously demonstrated high EGFR expression in NETs (13 (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in EGFR exons 18, 19, and 21 are associated in non-small-cell lung cancer (NSCLC) with response to the tyrosine kinase inhibitor (TKI) gefitinib (Lynch et al 2004, Paez et al 2004, whereas high EGFR copy number, determined by fluorescence in situ hybridization (FISH), is associated with sensitivity to gefitinib in NSCLC (Cappuzzo et al 2005a, Hirsch et al 2005 and to monoclonal antibodies cetuximab and panitumumab in colorectal cancer (Moroni et al 2005, Sartore-Bianchi et al 2007, Cappuzzo et al 2008. In this study, activating mutations and FISH-determined copy number of EGFR (a protein expressed in 91% of GI neuroendocrine tumor primaries as well as 98% of metastases (Papouchado et al 2005)) were investigated as markers for response to anti-EGFR inhibitors and antibodies. Mutations in KRAS codons 12 and 13 are associated with lack of response to cetuximab (Lievre et al 2006, De Roock et al 2008, Karapetis et al 2008) and panitumumab (Amado et al 2008) in colorectal cancer, and to TKIs gefitinib and erlotinib in lung cancer (Eberhard et al 2005, Pao et al 2005, Massarelli et al 2007; therefore, KRAS mutations associated with nonresponse to anti-EGFR therapy were also assessed in NETs.…”
Section: Introductionmentioning
confidence: 99%
“…Typical and atypical bronchopulmonary carcinoids [129] and gastrointestinal-neuroendocrine tumours (GI-NETs) and P-NETs present and over-regulate EGFRs. [130] [ Figure 1] Papouchado et al [131] in particular, described a higher presence of EGFR (> 91%) in GI-NETs, especially rectal NETs, than in P-NETs (< 25%).…”
Section: Vegf and Its Receptor Inhibitorsmentioning
confidence: 99%